Ganoderma: A Cancer Immunotherapy Review - Cao, Yu; Xu, Xiaowei; Liu, Shujing; Huang, Linfang; Gu, Jian (Frontiers in Pharmacology, 2018)
Ganoderma is a significant source of natural fungal medicines and has been used for the treatment of various diseases for many years. However, the use of Ganoderma in cancer immunotherapy is poorly elucidated. In this study, we have analyzed 2,398 English-language papers and 6,968 Chinese-language papers published between 1987 and 2017 by using bibliometrics. A steady growth in the number of publications was observed before 2004, followed by an exponential increase between 2004 and 2017. The most common category for publications about Ganoderma was “Pharmacology & Pharmacy”, in which immunomodulation (25.60%) and cancer treatment (21.40%) were the most popular subcategories. Moreover, we have provided an overview of the bioactive components and combinatorial immunomodulatory effects for the use of Ganoderma in the treatment of cancer, including the major pathways of immune cells. Immunomodulatory protein and polysaccharides are the key bioactive factors responsible for cancer immunotherapy, and the NF-κB and MAPK pathways are the most comprehensively investigated major pathways. Our results indicate that Ganoderma has a broad-spectrum application for the treatment of cancer through the regulation of the immune system. This review provides guidance for future research into the role of Ganoderma in cancer immunotherapy.